EphB4 and ephrinB2 act in opposition in the head and neck tumor microenvironment - Shilpa Bhatia; Diemmy Nguyen; Laurel B. Darragh; Benjamin Van Court; Jaspreet Sharma; Michael W. Knitz; Miles Piper; Sanjana Bukkapatnam; Jacob Gadwa; Thomas E. Bickett; Shiv Bhuvane; Sophia Corbo; et al. (Nature Communications, 2022)
EphrinB2 and its receptor EphB4 are highly expressed in head and neck squamous cell carcinoma (HNSCC) and disrupting EphB4-ephrinB2 interaction generates sub-optimal outcomes. Here, compartmental targeting of EphB4 and ephrinB2 in HNSCC cancer cell and endothelial compartments suggests that ephrinB2 acts as a tumor promoter and EphB4 as a tumor suppressor.